2007
DOI: 10.1038/sj.jp.7211879
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal pressure with high-flow nasal cannulae in premature infants

Abstract: Objective: The aim of this study was to measure pharyngeal pressures in preterm infants receiving high-flow nasal cannulae.Study Design: A total of 18 infants were studied (median gestational age 34 weeks, weight 1.619 kg). A catheter-tip pressure transducer was introduced into the nasopharynx. Flow was sequentially increased to a maximum of 8 l min À1 and decreased to a minimum of 2 l min À1 .Result: There was a strong association between pharyngeal pressure and both flow rate and infant weight (P<0.001, r 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
146
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(168 citation statements)
references
References 17 publications
12
146
1
9
Order By: Relevance
“…Both Kubicka et al (2008) and Wilkinson et al (2008) verify that there is a linear relationship between the infant's weight and the flow rate with the pressure generated. However, they have contradictory results regarding mouth closure.…”
Section: Hfncmentioning
confidence: 77%
See 1 more Smart Citation
“…Both Kubicka et al (2008) and Wilkinson et al (2008) verify that there is a linear relationship between the infant's weight and the flow rate with the pressure generated. However, they have contradictory results regarding mouth closure.…”
Section: Hfncmentioning
confidence: 77%
“…In a different study, Wilkinson, Andersen, and Holberton (2008) LPM can produce clinically significant CPAP levels in preterm infants. Both Kubicka et al (2008) and Wilkinson et al (2008) verify that there is a linear relationship between the infant's weight and the flow rate with the pressure generated.…”
Section: Hfncmentioning
confidence: 92%
“…15,16 Studies in infants have shown that the amount of pressure delivered to the pharynx, and possibly to the lungs, is associated with higher flows and lower infant weight. 1,[3][4][5] These human studies have also documented significant interpatient variability in measured pressures. Lampland et al 3 reported a 161-1,885% interpatient coefficient of variation in their study comparing pressures generated by HFNC with nasal CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…2 HFNC also provides a continuous distending pressure, and it has been shown to be comparable with distending pressure produced by nasal CPAP. 1,[3][4][5] The distending pressure produced by HFNC is unknown at the bedside when it is not continuously monitored. Monitoring this distending pressure is paramount, since this continuous pressure changes with changes in pulmonary mechanics, such as resistance and compliance, and it is extremely variable between patients.…”
Section: Introductionmentioning
confidence: 99%
“…This CPAP effect was first noted by Locke et al in 1993, 1 and since has been well documented by a number of authors. [2][3][4][5][6][7][8][9] The greatest fear clinicians have regarding high-flow therapy is the lack of knowledge of how much pressure is delivered to the airways. Although concern has been raised by some authors 6,7 regarding the CPAP pressure in premature infants, particularly those weighing Ͻ 1,000 g, similar concerns have not been documented in the adult population.…”
mentioning
confidence: 99%